2019
DOI: 10.1111/apt.15541
|View full text |Cite
|
Sign up to set email alerts
|

The Shock Index is not accurate at predicting outcomes in patients with upper gastrointestinal bleeding

Abstract: Summary Background Acute upper gastrointestinal bleeding (UGIB) remains a major cause of hospital admission worldwide. The recent UK National Confidential Enquiry into Patient Outcome and Death (NCEPOD) report on severe gastrointestinal bleeding used the Shock Index to assess bleeding severity and found an association between Shock Index and mortality. However, this has never been prospectively validated as a predictor of outcome in UGIB. Aims To compare the Shock Index with existing pre‐endoscopic UGIB risk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Gastrointestinal bleeding is a common clinical condition, most of which can be identified by gastroscopy and colonoscopy [1]. e American Gastroenterological Association defines obscure gastrointestinal bleeding (OGIB) as persistent or recurrent gastrointestinal bleeding, in which no lesion can be detected by conventional gastroscopy or fiberoptic colonoscopy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal bleeding is a common clinical condition, most of which can be identified by gastroscopy and colonoscopy [1]. e American Gastroenterological Association defines obscure gastrointestinal bleeding (OGIB) as persistent or recurrent gastrointestinal bleeding, in which no lesion can be detected by conventional gastroscopy or fiberoptic colonoscopy [2].…”
Section: Introductionmentioning
confidence: 99%
“…9 In a study by Saffouri et al, the shock index was found to have weaker performance than other scoring systems for predicting 30-day mortality among patients with acute upper GI bleeding. 26 In our study, we found that the shock index and AIMS-65 score had statistically better results than the Rockall and Glasgow- found that the performance of the shock index was weak with regard to predicting the 30-day mortality rate in their study. 26 We think that the fact that the patients included in their study were younger and had less comorbidity may have caused that result.…”
Section: Discussionmentioning
confidence: 49%
“…While predicting need for hospitalization, cut-off values for SI and PR were calculated as >0.68 and >80 beats/min, respectively. Saffouri et al (21) found that SI is useful when predicting need for major transfusion, which means more than 4 units of erythrocyte suspension, in patients with upper gastrointestinal hemorrhage. El-Menyar et al (22) reported that SI can be used to predict massive BT or laparotomy requirement and mortality in trauma patients.…”
Section: Discussionmentioning
confidence: 99%